2022
DOI: 10.1093/jme/tjac123
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Leishmaniasis in an Endemic Area of Northeast Brazil: Implications for Intervention Actions

Abstract: This study aimed to analyze the spatiotemporal distribution of leishmaniases, and contribute to the knowledge of their epidemiological dynamics from 2007 to 2017 in the municipality of Caxias, Maranhão, Northeast Brazil. Data on American tegumentary leishmaniasis (ATL) and human visceral leishmaniasis (HVL) were obtained in the Epidemiological Surveillance Sector of Caxias, while data on canine visceral leishmaniasis (CVL) were obtained in the Zoonoses Surveillance Unit. For data analysis and spatial represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…The study demonstrated a westward and centripetal expansion of the disease in Brazil. Similar results have been reported by Guimaraes et al [24]. In addition, analysis of epidemiological characteristics indicated a resurgence of VL in recent years.…”
Section: Discussionsupporting
confidence: 90%
“…The study demonstrated a westward and centripetal expansion of the disease in Brazil. Similar results have been reported by Guimaraes et al [24]. In addition, analysis of epidemiological characteristics indicated a resurgence of VL in recent years.…”
Section: Discussionsupporting
confidence: 90%